Infectious Complications After Transcatheter Aortic Valve Implantation in Geriatric Patients - Ozer-Balin, Safak; Balin, Mehmet; Karaca, Ilgin (Doc Design Informatics Co Ltd, 2020)
Objective: Transcatheter aortic valve implantation (TAVI) is a preferred alternative method for valve replacement in patients with high-risk symptomatic aortic stenosis, especially older patients. Although TAVI provides apparent benefits, it is known to be associated with some complications such as infection, paravalvular insufficiency, and thrombosis. In this study, we aimed to evaluate infection related complications of the patients undergoing TAVI. Methods: In the Cardiology Clinic of our hospital, 107 geriatric patients with severe aortic stenosis between the years 2014 and 2018 were treated with TAVI. For this purpose, groin areas of patients were disinfected from the belly level to the knees and covered in a sterile manner. The femoral artery was reached through a 3 cm incision in the groin area where the TAVI attempt was made. The catheter was advanced from the main-femoral artery to the abdominal aorta. The bioprosthesis was then implanted into the aortic annulus. 50% of the bioprosthetic valve was placed in the ascending aorta and 50% in the aortic annulus. Demographic data, clinical and laboratory findings of the patients were obtained by retrospective screening. Results: A total of 107 patients with a mean age of 80.2 (65-95) years were included in the study, and 59 (55.1%) were male. Infection-related complications developed in 6 (5.6%) patients. During the procedure, 104 (97.1%) patients had cefazolin, and 3 (2.8%) had vancomycin as systemic antibiotic prophylaxis. Local access site infection developed in four (3.7%) patients. All patients had Escherichia coli at the wound site. Bioprothesis-associated infective endocarditis developed in 2 (1.8%) patients. Conclusions: Infection-related complications were rare after TAVI. This situation supports the fact that it can be applied safely in patients with advanced age in terms of infection.
Geriyatrik hastalarda transkateter aort kapağı implantasyonu sonrası gelişen infeksiyöz komplikasyonlar
Keywords: Transcatheter aortic valve replacement; infectious complications; endocarditis